IMPLICATIONS OF THE APPLICATION OF THE PROJECT-BASED LEARNING MODEL REVIEWED FROM THE INDEPENDENT CURRICULUM IN DEVELOPING STUDENT LEARNING ACTIVITIES AT SCHOOL - Nisak, Ainun; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article aims to find out how Project Based Learning is implemented at SMPIT Permata Kraksaan in terms of the Merdeka Curriculum and how active students are in Islamic Religious Education through Project Based Learning. The method used in this research is a qualitative method with a case study approach. The presentation of this research report illustrates that the learning model implemented is in accordance with the achievements of creativity and the independent curriculum, because students can accept Project Based Learning as a learning model that helps them develop their creativity in learning according to the independent curriculum. Thus, there is a recommendation for other researchers, that this research only reviews a small part of the problems related to Project Based Learning and student creativity. It is recommended that other researchers can carry out further research and carry it out better. Recommendations for educators are that they can prepare this learning model in a more conceptual way so that students' creative achievements can be maximized.